A comparative analysis between the quick response manufacturing and time-based competition methodologies - Emboava, Fábio Nogueira; Cardoso, Rodolfo; Tammela, Iara (Brazilian Journal of Operations & Production Management, 2017)
This article compares the Quick Response Manufacturing and Time-Based Competition methodologies and identifies their similarities and differences. This investigation deepens our understanding in terms of Quick Response Manufacturing pursuing a theoretical framework for applications in Brazilian companies. Data was collected from publications aimed at presenting and discussing the tactics and approaches of the methodologies. Similarity and difference classification tables are presented. The results reveal that 67% of all approaches compared were classified as analogous and 19% were not analogous. In addition, 14% of approaches presented the non-existence of similarities.